Indian Mathematics : Engaging with the World from Ancient to Modern Times - Joseph, George Gheverghese (Singapore : World Scientific Pub. Co., 2016)
"Indian Mathematics gives a unique insight into the history of mathematics within a historical global context. It builds on research into the connection between mathematics and the world-wide advancement of economics and technology. Joseph draws out parallel developments in other cultures and carefully examines the transmission of mathematical ideas across geographical and cultural borders."--Publisher's website.
Title from PDF file title page (viewed September 29, 2016).
Includes bibliographical references (p. 467-477) and indexes.
Electronic reproduction.
Mode of access: World Wide Web.
Keywords: Mathematics -- India -- History; Mathematics -- India; Mathematics, Medieval; Electronic books